A Systematic Review of Cognitive Function in First-Episode Psychosis, Including a Discussion on Childhood Trauma, Stress, and Inflammation - Aas, Monica; Dazzan, Paola; Mondelli, Valeria; Melle, Ingrid; Murray, Robin M.; Pariante, Carmine M. (Frontiers in Psychiatry, 2014)
OBJECTIVE: To carry out a systematic review of the literature addressing cognitive functions in first-episode psychosis, divided into domains. Although this is not a full “cognitive-genetics-in-schizophrenia review”, we will also include putative ideas of mechanism(s) behind these impairments, focusing on how early stress, and genetic vulnerability may moderate cognitive function in psychosis. METHOD: Relevant studies were identified via computer literature searches for research published up to and including January 2013, only case-control studies were included for the neurocognitive meta-analysis. RESULTS: Patients with first-episode psychosis present global cognitive impairment compared to healthy controls. The largest effect size was observed for verbal memory (Cohen’s d effect size=2.10), followed by executive function (effect size =1.86), and general IQ (effect size =1.71). However, effect sizes varied between studies. CONCLUSION: Cognitive impairment across domains, up to severe level based on Cohen’s effect size, is present already in first-episode psychosis studies. However, differences in levels of impairment are observed between studies, as well as within domains, indicating that further consolidation of cognitive impairment over the course of illness may be present. Cognitive abnormalities may be linked to a neurodevelopmental model including increased sensitivity to the negative effect of stress, as well as genetic vulnerability. More research on this field is needed.